Life and death: social perspectives on biblical bodies - Stavrakopoulou, Francesca (The Hebrew Bible in Social Perspective Ser., 2021)
Cover -- Series Page -- Title Page -- Contents -- Figures -- Contributors -- Editor's Note -- Abbreviations -- Chapter One The materiality of life and the sociality of death: An introduction -- The chapters -- References -- Part One Praxis and materiality -- Chapter Two Blood and hair: Body management and practice -- Blood -- Hair -- Closing thoughts -- References -- Chapter Three Wherever the corpse is, there the vultures will gather -- Vulture and corpse at Çatalhöyük -- The Stele of Vultures from Girsu -- Birds, corpses and Gog's burial in Ezekiel 39 -- Conclusion -- References -- Chapter Four 'Know well the faces of your sheep': Animal bodies and human bodies -- References -- Part Two Value, status and power -- Chapter Five Birthing new life: Israelite and Mesopotamian values and visions of the preborn child1 -- The Mesopotamian child in potentia: Medical sources -- The child and the gods in the Mesopotamian domestic cult -- The Hebrew Bible -- Jeremiah 1.4-5 -- Psalm 139.13-15 and Job 10.8-11 -- Conclusions -- References -- Chapter Six Persons with disabilities, unprotected parties and Israelite household structures -- The idealized Israelite household structure in the Pentateuch -- Unprotected parties without allotted land as an inalienable inheritance in the household structure -- Vulnerable and dependent but protected parties within the Israelite household structure -- Rhetorical goals and issues addressed in Lev. 19.14, Deut. 27.18, Job 29.12-16 and Ps. 146.8 -- Conclusions -- References -- Chapter Seven Modifying manly bodies: Mourning and masculinities in Ezra 9-10 -- Ezra the man -- Ezra the mourner -- Modifying manly bodies -- Embodying subordination -- The power of mourning -- Reconfiguring community -- 'Rehabilitating' divine masculinity -- Conclusion -- References -- Chapter Eight The wisdom of ageing -- The vocabulary of ageing.